1999
DOI: 10.1007/s002489900133
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rates of Marine Bacterial Isolates on Particulate Organic Substrates Solubilized by Freely Released Extracellular Enzymes

Abstract: > Abstract Growth rates of marine bacterial isolates on particulate organic substrates were measured using a novel apparatus which restricts bacterial cells to the uptake of hydrolysate produced from particulate substrates only by enzymes that are actively released from the bacterium into the culture medium. Significant, varying growth rates were measured for four different marine bacteria, using three different, ecologically significant particulate organic substrates (preparations of amylopectin, chitin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Vetter & Deming (1999) reported that released bacterial EE could produce sufficient hydrolysate from POC to support growth in the absence of any other significant source of DOC and without direct contact between the cell and particulate substrate. These empirical results obtained by Vetter & Deming (1999) support the model-based predictions formulated in an earlier paper (Vetter et al 1998), suggesting that dissolved EE are advantageous when bacteria are attached to particles and when the substrate is within a well-defined distance from the enzyme source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vetter & Deming (1999) reported that released bacterial EE could produce sufficient hydrolysate from POC to support growth in the absence of any other significant source of DOC and without direct contact between the cell and particulate substrate. These empirical results obtained by Vetter & Deming (1999) support the model-based predictions formulated in an earlier paper (Vetter et al 1998), suggesting that dissolved EE are advantageous when bacteria are attached to particles and when the substrate is within a well-defined distance from the enzyme source.…”
Section: Discussionmentioning
confidence: 99%
“…The release of EE into particles by particle-associated prokaryotes might help in maintaining relatively high metabolic activity as compared to their free-living counterparts. In fact, bacterial foraging theory suggests that independent of possible assemblage differences, individual bacteria may produce more EE in diffusionally constrained space such as particle aggregates, where the return of hydrolysate is potentially high (Vetter et al 1998) or, when confronted with polymeric organic matter (Chrost 1991, Vetter & Deming 1999. Moreover, Allison (2005) argued that microbes releasing EE have a competitive advantage over other microbes in environments with low rates of enzyme diffusion, such as sediments or particles.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments show that pure cultures of marine bacteria release enzymes into the surrounding media (Vetter and Deming, 1999;Alderkamp et al, 2007). High levels of dissolved endopeptidase activity in coastal seawater (Obayashi and Suzuki, 2008) also underscore the importance of cell-free enzymes in the ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, presence of cellulolytic and hemi-cellulolytic bacteria in one particular region and their absence in other region should indicated presence of wide-ranging organic matter in each region (Khanderparker et al, 2011). Previous research has also put forth a widely accepted concept that hydrolytic enzymes are induced by presence of polymeric substrates (Chrost, 1991;Vetter and Deming, 1999). It was observed that the genus Bacillus and Vibrio were the dominant hemicellulase and cellulase producers in both the estuaries.…”
Section: Api 20e* Strains Onpg Adh Odc Cit Ure Tda Ind Vp Gel Glu Manmentioning
confidence: 99%